Self-heating molecular sieve catalyst covered by oil-proof film and preparation method of self-heating molecular sieve catalyst
By using self-heating molecular sieve catalyst covered with oil-proof film and using combinations of materials such as diatomaceous earth, the catalyst can effectively adsorb and remove grease and gel after being covered with oil film or colloid, solving the deactivation of existing catalysts Problem, improving the purification effect.
Patent Information
- Application Number
- CN202411604068.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
After the existing molecular sieve catalyst is covered with oil film or colloid, the pores are blocked and the adsorption function is ineffective, and it is impossible to effectively remove impurities in oil-containing gases.
The self-heating molecular sieve catalyst covered with an oil-proof film composed of diatomaceous earth, zeolite powder, kaolin, graphene and heating agent is prepared through grinding, kneading, extrusion granulation and roasting steps to realize the self-expression function of the catalyst and Adsorption and desorption separation effects of oils and greases.
After being covered with oil film or gum, the catalyst can soften and adsorb oil and gum through self-heating function to ensure effective adsorption and purification of water and other impurities, solving the problem of catalyst deactivation.
Smart Images

Figure CN119488939A_ABST
Abstract
Description
Technical Field
[0002] The invention relates to the technical field of molecular sieve catalysts, in particular to a self-heating molecular sieve catalyst covered with an oil-proof film and a preparation method thereof. Background Art
[0003] Molecular sieve catalysts are used for the purification of chemical products, especially chemical gas products. They are often required to remove impurities such as grease, colloid and water to achieve the adsorption and desorption separation effect of molecular sieve catalysts. However, when facing gases containing grease and colloid, the existing molecular sieve catalysts will cause pore blockage once the outer surface is covered by oil film or colloid, and even the most easily adsorbed polar molecule water cannot be absorbed. Because the most feared thing for adsorbents and catalysts is that the grease will wrap the surface of the adsorbent and catalyst and lose its activity. Once the catalyst adsorption is blocked, the entire catalytic adsorption effect will fail.
[0004] Chemical products on the domestic market that carry oil, grease and gum include coal-to-hydrogen, coking exhaust gas, etc., which account for more than 30% of the market. If the above problems can be solved, it will not only effectively improve the production and economic benefits of enterprises, but also make significant contributions to environmental protection, energy conservation and emission reduction. Summary of the invention
[0005] The present invention aims to at least partially overcome the above technical problems and / or other potential problems existing in the prior art: to provide a self-heating molecular sieve catalyst that is resistant to oil film coverage and a preparation method thereof. The molecular sieve catalyst of the present invention can effectively solve the problem of molecular sieve catalyst being inactivated by being covered by oil film and colloid during use. It can achieve the effect of first absorbing grease and colloid, and then absorbing water and other impurities.
[0006] The technical solution of the present invention is as follows: a self-heating molecular sieve catalyst covered with an oil-proof film is mainly prepared from the following raw materials in parts by weight: 20-30 parts of diatomaceous earth; 25-32 parts of zeolite powder; 25-30 parts of kaolin; 5-8 parts of graphene; and 10-25 parts of a heating agent.
[0007] As an optimization, the exothermic agent is one or more of calcium oxide, calcium hydroxide and phosphorus pentoxide.
[0008] Most preferably, the zeolite powder is Nax type zeolite powder.
[0009] As an optimization, the diatomaceous earth is made by drying and crushing aged diatom mud to a particle size greater than 800 meshes, and the diatom mud is aged for 6-10 months in a light-proof closed space at a controlled temperature of 20-30°C and a humidity of 50-70%.
[0010] The present invention also provides a method for preparing a self-heating molecular sieve catalyst covered with an oil-proof film, comprising the following steps: 1) Weigh the following raw materials according to the above weight ratio: diatomaceous earth, zeolite powder, kaolin, graphene, and exothermic agent; 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh, and then pelletized or extruded, and the pellets are naturally dried for 3-7 days, then dried at 120-180° C. for 2-4 hours, calcined and activated at 580-620° C. for 2-3 hours, and cooled to room temperature to obtain a catalyst carrier for use; 3) Add the exothermic agent into water, boil for 4-6 hours, and then cool to room temperature to obtain an exothermic agent impregnation solution. Then, place the catalyst carrier prepared in step 2) into the exothermic agent impregnation solution and immerse it for 12-24 hours. After taking it out and drying it, it is calcined at a constant temperature of 580-620°C for 6-8 hours for regeneration and activation to obtain a self-heating molecular sieve catalyst covered with an oil-proof film.
[0011] As an optimization, the water in the exothermic agent impregnation solution in step 3) of the above preparation method accounts for 60-65% of the weight of the catalyst carrier.
[0012] The present invention also provides another method for preparing a self-heating molecular sieve catalyst covered with an oil-proof film, comprising the following steps: 1) Weigh the following raw materials according to the weight ratio: diatomaceous earth, zeolite powder, kaolin, graphene, and heating agent; 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh and then put into a kneader, 38-40% of water of the total amount of the material is added, and kneaded for 2-4 hours to form a mud material, and then the exothermic agent is dissolved in water and put into the kneader, and kneaded again for 2-3 hours, and then the mud material is put into an extruder for extrusion granulation, and the extruded columnar particles are naturally dried for 3-7 days, and then dried at 120-180°C for 2-4 hours, calcined and activated at a temperature of 580-620°C for 2-3 hours, and cooled to room temperature to obtain a self-heating molecular sieve catalyst covered with an oil-proof film.
[0013] The beneficial effects of the present invention are as follows: in order to solve the problem that the molecular sieve catalyst is covered by oil film and colloid and deactivated, the present invention first selects diatomaceous earth, which is a porous and large specific surface material, as a raw material to deepen the adsorption and desorption separation effect of the catalyst on grease, and then utilizes the combination of graphene and zeolite molecular sieve to further improve the adsorption and desorption performance of water, and the effect of purification, desorption and catalytic degreasing; in particular, the self-heating function of the molecular sieve catalyst during operation is realized, so that the grease and colloid components in the main gas are first adsorbed, and then water and other impurities are adsorbed. The use of the above raw materials to prepare the catalyst can achieve the purpose of first adsorbing and desorbing grease and colloid in the gas, and then adsorbing water. The principle is: in the molecular sieve catalyst, once the water-carrying gas enters the molecular sieve catalyst packing layer in the device, the raw material reacts with part of the water to release heat energy, and a large amount of heat release temperature reaches 60-90°C, which instantly softens, decomposes and dilutes the grease and colloid, and then the diatomaceous earth with a large specific surface material adsorbs and separates the diluted grease and colloid, and the remaining gas moisture is completely adsorbed by zeolite. Diatomaceous earth has a larger specific surface area, providing more adsorption sites; this porous structure is larger, and its adsorption capacity for water molecules is relatively weakened. At this time, polar water smoothly enters the zeolite section of the water adsorption area with the airflow and is adsorbed at the fastest speed. After the adsorption is successfully completed, the molecular sieve catalyst is burned and desorbed to achieve regeneration.
[0014] The catalyst of the present invention releases heat when it meets water because it includes the following raw materials: calcium oxide (CaO) and calcium hydroxide Ca(OH)2 are added and then roasted to form a molecular sieve catalyst, calcium oxide can be uniformly formed during the process. Calcium oxide is hygroscopic and can be used as a desiccant, adsorbent, catalyst, etc. It releases a large amount of heat energy when it reacts with water. Phosphorus pentoxide (P2O5) releases heat when it reacts with water. Phosphorus pentoxide is a highly hygroscopic substance and is often used as a desiccant and dehydrating agent to effectively remove (H2O) from the gas, playing a role in the drying and purification process. It can also neutralize the acidic pore structure of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a physical morphology picture of the self-heating molecular sieve catalyst covered with an oil-proof film prepared in Example 1.
[0016] Figure 2 This is a physical morphology picture of the self-heating molecular sieve catalyst covered with an oil-proof film prepared in Example 4. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0018] Example 1 The self-heating molecular sieve catalyst covered with oil-proof film was prepared as follows: 1) Weigh the following raw materials according to the weight ratio: 30kg diatomite; 30kg Nax zeolite powder; 25kg kaolin; 5kg graphene; 10kg calcium oxide. The diatomite is made by drying and crushing aged diatom mud to a particle size greater than 800 mesh, and the diatom mud is aged for 6-10 months in a light-proof closed space at a temperature of 20-30°C and a humidity of 50-70%.
[0019] 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh and then put into a kneader, 38% of the total amount of water is added, and kneaded for 2 hours to form a mud material, and then calcium oxide is dissolved in water and put into the kneader, and kneaded again for 2 hours, and then the mud material is put into an extruder for extrusion granulation, and the extruded columnar particles are naturally dried for 7 days, and then dried at 120-180°C for 2 hours, calcined and activated at 580°C for 3 hours, and cooled to room temperature to obtain a self-heating molecular sieve catalyst covered with an oil-proof film. The catalyst morphology is as follows Figure 1 shown.
[0020] The testing indicators of molecular sieve catalyst are as follows: compressive strength 100-150N / particle; bulk density 720-780kg / m 3 ; Specific surface area 720-780m 2 / g; degrease amount 10-13wt%; static water adsorption 26.5wt%; dynamic water adsorption 15wt%; saturated water adsorption 66wt%; pore volume 0.70-0.95cm 3 / g; porosity 65-76%.
[0021] Example 2 The self-heating molecular sieve catalyst covered with oil-proof film was prepared as follows: 1) Weigh the following raw materials according to the weight ratio: 27kg diatomite; 30kg Nax zeolite powder; 25kg kaolin; 8kg graphene; 10kg calcium hydroxide. The diatomite is made by drying and crushing aged diatom mud to a particle size greater than 800 mesh, and the diatom mud is aged for 6-10 months in a light-proof closed space at a temperature of 20-30°C and a humidity of 50-70%.
[0022] 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh and then put into a kneader, 38% of the total amount of water is added, and the mixture is kneaded for 4 hours to form a mud material. Then, calcium hydroxide is dissolved in water of equal specific gravity and put into the kneader, and kneaded again for 3 hours. The mud material is then put into an extruder for extrusion granulation. The extruded columnar particles are naturally dried for 5 days, then dried at 120-180°C for 4 hours, calcined and activated at 620°C for 3 hours, and cooled to room temperature to obtain a self-heating molecular sieve catalyst covered with an oil-proof film.
[0023] The testing indicators of molecular sieve catalyst are as follows: compressive strength 130-200N / particle; bulk density 720-750kg / m 3 ; Specific surface area 730-790m 2 / g; degrease amount 10-12.7wt%; static water adsorption 26.8wt%; dynamic water adsorption 16wt%; saturated water adsorption 68wt%; pore volume 0.72-0.98cm 3 / g; porosity 65-78%.
[0024] Example 3 The self-heating molecular sieve catalyst covered with oil-proof film was prepared as follows: 1) Weigh the following raw materials according to the weight ratio: 27kg diatomite; 30kg Nax zeolite powder; 25kg kaolin; 8kg graphene; 10kg phosphorus pentoxide. The diatomite is made by drying and crushing aged diatom mud to a particle size greater than 800 mesh, and the diatom mud is aged for 6-10 months in a light-proof closed space at a temperature of 20-30°C and a humidity of 50-70%.
[0025] 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh and then put into a kneader, 38% of the total amount of water is added, and the mixture is kneaded for 4 hours to form a mud material. Then, phosphorus pentoxide is dissolved in water and put into the kneader, and kneaded again for 3 hours. The mud material is then put into an extruder for extrusion granulation. The extruded columnar particles are naturally dried for 5 days, then dried at 120-180°C for 4 hours, calcined and activated at 620°C for 3 hours, and cooled to room temperature to obtain a self-heating molecular sieve catalyst covered with an oil-proof film.
[0026] The testing indicators of molecular sieve catalyst are as follows: compressive strength 120-180N / particle; bulk density 720-750kg / m 3 ; Specific surface area 730-780m 2 / g; degrease amount 11-14.5wt%; static water adsorption 27.3wt%; dynamic water adsorption 16.0wt%; saturated water adsorption 66.0wt%; pore volume 0.8-1.05cm 3 / g; porosity 65-79%.
[0027] Example 4 The self-heating molecular sieve catalyst covered with oil-proof film was prepared as follows: 1) Weigh the following raw materials according to the weight ratio: 20kg diatomite; 25kg Nax zeolite powder; 25kg kaolin; 5kg graphene; 25kg calcium oxide. The diatomite is made by drying and crushing aged diatom mud to a particle size greater than 800 mesh. The diatom mud is aged for 6-10 months in a light-proof, closed space at a temperature of 20-30°C and a humidity of 50-70%. The aged diatomite not only increases the specific surface area and porosity, but also can filter, adsorb and decompose impurities such as grease and glue under hydrophobic conditions. Combined with graphene, it can increase the reaction rate of the catalyst and improve the stability and selectivity of the catalyst.
[0028] 2) First, the diatomaceous earth, Nax zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh, and pelletized using a pelletizer. The spherical particles are naturally dried for 7 days, then dried at 120-180° C. for 2 hours, calcined and activated at 620° C. for 3 hours, and cooled to room temperature to obtain a catalyst carrier for use; 3) Add calcium oxide to water and boil for 4 hours, then cool to room temperature to obtain a heat-generating agent impregnation solution. Then, place the catalyst carrier prepared in step 2) in the heat-generating agent impregnation solution and immerse for 24 hours. After taking it out and drying it, it is calcined at 580°C for 8 hours for regeneration and activation to obtain a self-heating molecular sieve catalyst covered with an oil-proof film. In step 3), the water in the heat-generating agent impregnation solution accounts for 60% of the weight of the catalyst carrier. The prepared molecular sieve catalyst has a morphology such as Figure 2 shown.
[0029] The testing indicators of molecular sieve catalyst are as follows: compressive strength 130-200N / particle; bulk density 720-770kg / m 3 ; Specific surface area 730-780m 2 / g; degrease amount 10-15wt%; static water adsorption 27.5wt%; dynamic water adsorption 17wt%; saturated water adsorption 72wt%; pore volume 0.70-1.10cm 3 / g; porosity 65-79%.
[0030] Example 5 The self-heating molecular sieve catalyst covered with oil-proof film was prepared as follows: 1) Weigh the following raw materials according to the weight ratio: 20kg diatomite; 32kg Nax zeolite powder; 25kg kaolin; 5kg graphene; 18kg calcium oxide. The diatomite is made by drying and crushing aged diatom mud to a particle size greater than 800 mesh, and the diatom mud is aged for 6-10 months in a light-proof closed space at a temperature of 20-30°C and a humidity of 50-70%.
[0031] 2) First, the diatomaceous earth, Nax zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh, and then put into a kneader, 40% of the total amount of water is added, and the slurry is kneaded for 4 hours to form a slurry, and then the slurry is put into an extruder for extrusion and granulation. The extruded columnar particles are naturally dried for 7 days, and then dried at 120-180° C. for 2 hours, calcined and activated at 620° C. for 3 hours, and cooled to room temperature to obtain a catalyst carrier for use; 3) Add calcium oxide to water, boil for 4 hours, and then cool to room temperature to obtain a heat-generating agent impregnation liquid. Then, place the catalyst carrier prepared in step 2) in the heat-generating agent impregnation liquid and immerse for 24 hours. After being taken out and dried, the catalyst carrier is calcined at a constant temperature of 580°C for 8 hours for regeneration and activation to obtain a self-heating molecular sieve catalyst covered with an oil-proof film. In step 3), the water in the heat-generating agent impregnation liquid accounts for 60% of the weight of the catalyst carrier.
[0032] The testing indicators of molecular sieve catalyst are as follows: compressive strength 120-180N / particle; bulk density 720-760kg / m 3 ; Specific surface area 730-790m 2 / g; degrease amount 16-19wt%; static water adsorption 28wt%; dynamic water adsorption 17.2wt%; saturated water adsorption 72.5wt%; pore volume 0.80-1.15cm 3 / g; porosity 65-81%.
[0033] Comparative Example 1 The molecular sieve catalyst was prepared by the following steps: 1) Weigh the following raw materials according to the weight ratio: 20kg diatomite; 32kg Nax zeolite powder; 25kg kaolin; 5kg graphene. The diatomite is made by drying and crushing aged diatom mud to a particle size greater than 800 mesh, and the diatom mud is aged for 6-10 months in a light-proof closed space at a temperature of 20-30°C and a humidity of 50-70%.
[0034] 2) First, the diatomaceous earth, Nax zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh, and then put into a kneader, 40% of water of the total amount of the material is added, and the slurry is kneaded for 4 hours to form a mud material, and then the mud material is put into an extruder for extrusion granulation. The extruded columnar particles are naturally dried for 7 days, and then dried at 120-180°C for 2 hours, calcined and activated at 620°C for 3 hours, and cooled to room temperature to obtain a molecular sieve catalyst control group.
[0035] The test indicators of the molecular sieve catalyst control group are as follows: compressive strength 110-120N / grain; bulk density 720-750kg / m 3 ; Specific surface area 720-760m 2 / g; degrease amount 3-7wt%; static water adsorption 20wt%; dynamic water adsorption 15.5wt%; saturated water adsorption 56.0wt%; pore volume 0.70-0.90cm 3 / g; porosity 65-67%.
[0036] By comparing Comparative Example 1 with Example 5, it can be seen that due to the lack of exothermic agent in Comparative Example 1, the molecular sieve catalyst is immediately inactivated due to being covered by the oil film during operation, thereby greatly reducing the adsorption rate of grease and colloid components, thereby affecting the adsorption effect of other impurities in water.
[0037] The above are only examples of the features of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent exchange or equivalent replacement falls within the protection scope of the present invention.
Claims
1. A self-heating molecular sieve catalyst covered with an oil-proof film, characterized in that: The invention is mainly prepared from the following raw materials in parts by weight: 20-30 parts of diatomaceous earth; 25-32 parts of zeolite powder; 25-30 parts of kaolin; 5-8 parts of graphene; and 10-25 parts of heating agent.
2. The oil-proof film-covered self-heating molecular sieve catalyst according to claim 1, characterized in that: The exothermic agent is one or more of calcium oxide, calcium hydroxide and phosphorus pentoxide.
3. The oil-proof film-covered self-heating molecular sieve catalyst according to claim 1, characterized in that: The zeolite powder is Nax type zeolite powder.
4. The oil-proof film-covered self-heating molecular sieve catalyst according to claim 1, characterized in that: The diatomaceous earth is prepared by drying and crushing aged diatom mud to a particle size greater than 800 meshes. The diatom mud is aged for 6-10 months in a light-proof closed space at a controlled temperature of 20-30° C. and a humidity of 50-70%.
5. A method for preparing the self-heating molecular sieve catalyst covered with an oil-proof film as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Weigh the following raw materials according to the weight ratio: diatomaceous earth, zeolite powder, kaolin, graphene, and heating agent; 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh, and then pelletized or extruded, and the pellets are naturally dried for 3-7 days, then dried at 120-180° C. for 2-4 hours, calcined and activated at 580-620° C. for 2-3 hours, and cooled to room temperature to obtain a catalyst carrier for use; 3) Add the exothermic agent into water, boil for 4-6 hours, and then cool to room temperature to obtain the exothermic agent impregnation solution. Then, put the catalyst carrier prepared in step 2) into the exothermic agent impregnation solution and immerse it for 12-24 hours. After taking it out and drying it, it is calcined at a constant temperature of 580-620°C for 6-8 hours for regeneration and activation to obtain a molecular sieve catalyst covered with a self-heating oil-proof film.
6. The method for preparing the oil-proof film-covered self-heating molecular sieve catalyst according to claim 5, characterized in that: In step 3), the water in the exothermic agent impregnation liquid accounts for 60-65% of the weight of the catalyst carrier.
7. A method for preparing the self-heating molecular sieve catalyst covered with an oil-proof film as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Weigh the following raw materials according to the weight ratio: diatomaceous earth, zeolite powder, kaolin, graphene, and heating agent; 2) First, the diatomaceous earth, zeolite powder, kaolin and graphene in step 1) are mixed and ground to 500-800 mesh and then put into a kneader, 38-40% of water of the total amount of the material is added, and kneaded for 2-4 hours to form a mud material, and then the exothermic agent is dissolved in water and put into the kneader, and kneaded again for 2-3 hours, and then the mud material is put into an extruder for extrusion granulation, and the extruded columnar particles are naturally dried for 3-7 days, and then dried at 120-180°C for 2-4 hours, calcined and activated at a temperature of 580-620°C for 2-3 hours, and cooled to room temperature to obtain a self-heating oil-proof film-covered molecular sieve catalyst.